Immigration and improvements in American life expectancy - Arun S. Hendi; Jessica Y. Ho (Elsevier, 2021)
Despite the immigrant mortality advantage and the increasing share of the population born abroad, relatively little is known about how immigration has impacted trends in US life expectancy. How immigrants contribute to national life expectancy trends is of increasing interest, particularly in the context of an unprecedented stagnation in American mortality. We find that immigration increases US life expectancy by 1.5 years for men and 1.4 years for women. Over half of these contributions occur at the prime working ages of 25-64. The difference between foreign-born and US-born mortality has grown substantially since 1990, with the ratio of US-born to foreign-born mortality rates nearly doubling by 2017. In that year, foreign-born life expectancy reached 81.4 and 85.7 years for men and women, respectively-7.0 and 6.2 years higher than their US-origin counterparts. These life expectancy levels are remarkable by most standards. Foreign-born male life expectancy exceeds that of Swiss men, the world leaders in male life expectancy. Life expectancy for foreign-born women is close to that of Japanese women, the world leaders in female life expectancy. The widening mortality difference between the US-born and foreign-born populations, coupled with an increase in the share of the population born abroad, has been responsible for much of the increase in national life expectancy in recent years. Between 2007 and 2017, foreign-born men and women were responsible for 44% and 60% of national life expectancy improvements. Between 2010 and 2017, immigrants experienced gains while the US-born experienced declines in life expectancy. Thus, nearly all of the post-2010 mortality stagnation is due to adverse trends among the US-born. Without immigrants and their children, national life expectancy in 2017 would be reduced to its 2003 levels. These findings demonstrate that immigration acts to bolster American life expectancy, with particularly valuable contributions at the prime working ages.